2004
DOI: 10.1016/j.cub.2004.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Scribble Forms a Tight Complex with the βPIX Exchange Factor

Abstract: Drosophila Scribble is implicated in the development of normal synapse structure and epithelial tissues, but it remains unclear how it plays a role and which process it controls. The mammalian homolog of Scribble, hScrib, has a primary structure and subcellular localization similar to that of its fly homolog, but its function remains unknown. Here we have used tandem mass spectrometry to identify major components of the hScrib network. We show that it includes betaPIX (also called Cool-1), a guanine nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
254
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(263 citation statements)
references
References 31 publications
6
254
0
3
Order By: Relevance
“…While Scribble knockdown did not affect Rac activation per se, it was required for Rac1 localization at the leading edge following scratchinduced migration, indicating that Scribble is essential for the appropriate polarized membrane localization of activated Rac1. In support of a direct role for Scribble in mediating Rac function, others have shown that Scribble can physically associate in a complex with Rac1 following stimulation of PC12 cells (Audebert et al, 2004). In addition, Scribble constitutively associates with the RacGEF bPix and the Arf-GAP protein GIT1 that was recently shown to be required for the restricted activation of Rac1 at the leading edge of migrating epithelial cells (Audebert et al, 2004;Nishiya et al, 2005).…”
Section: Regulation Of Directional Migration By Mammalian Scribblementioning
confidence: 95%
See 1 more Smart Citation
“…While Scribble knockdown did not affect Rac activation per se, it was required for Rac1 localization at the leading edge following scratchinduced migration, indicating that Scribble is essential for the appropriate polarized membrane localization of activated Rac1. In support of a direct role for Scribble in mediating Rac function, others have shown that Scribble can physically associate in a complex with Rac1 following stimulation of PC12 cells (Audebert et al, 2004). In addition, Scribble constitutively associates with the RacGEF bPix and the Arf-GAP protein GIT1 that was recently shown to be required for the restricted activation of Rac1 at the leading edge of migrating epithelial cells (Audebert et al, 2004;Nishiya et al, 2005).…”
Section: Regulation Of Directional Migration By Mammalian Scribblementioning
confidence: 95%
“…In support of a direct role for Scribble in mediating Rac function, others have shown that Scribble can physically associate in a complex with Rac1 following stimulation of PC12 cells (Audebert et al, 2004). In addition, Scribble constitutively associates with the RacGEF bPix and the Arf-GAP protein GIT1 that was recently shown to be required for the restricted activation of Rac1 at the leading edge of migrating epithelial cells (Audebert et al, 2004;Nishiya et al, 2005). This presents the intriguing possibility that Scribble and GIT1 associate in a complex with bPix to coordinately regulate the spatially restricted activation of Rac1.…”
Section: Regulation Of Directional Migration By Mammalian Scribblementioning
confidence: 95%
“…We recently characterized a bPIX-GIT1 complex bound to the PDZ domains of hScrib [31]. hScrib has four PDZ domains that interact with multiple partners [32].…”
Section: Introductionmentioning
confidence: 99%
“…De même les domaines PDZ semblent absolument nécessaires à la fonction de Scrib car leur suppression ou leur surexpression bloque totalement la polarisation des astrocytes en migration [14]. Les domaines PDZ permettent la liaison de nombreux partenaires parmi lesquels la protéine βPIX [26]. Dans les astrocytes, Scrib interagit de manière constitutive avec βPIX et cette interaction augmente au cours de la polarisation des cellules.…”
Section: L'interaction Cruciale De Scrib Avec Le Facteur D'échange Bpixunclassified